'Sad ol' mush': The Poetics and Politics of Porridge in Residential Schools in Canada. (3rd July 2022) - Gora, L. Sasha
ABSTRACT: In Indian School Days, Basil Johnston remembers eating watery porridge – 'sad ol' mush' – at St. Peter Claver School for Boys. A collaboration between the Canadian government and Christian churches to assimilate Indigenous children, residential schools served food that aligned with this mission. Zooming in on the history of the poetics and politics of porridge, this article weaves together a study of the food residential schools served with writing by survivors and from the genre of children's literature. It asks: How does breakfast connect to larger conflicts over land and power? And what role does children's culture play in this?